The ocrelizumab phase II extension trial suggests the potential to improve the risk: Benefit balance in multiple sclerosis - Baker, David; Pryce, Gareth; James, Louisa K.; Marta, Monica; Schmierer, Klaus (Multiple sclerosis and related disorders, 2020)
•Ocrelizumab phase II trial extension data has 18-month post-drug follow-up.•Annualized relapse rate seems to remain low during the drug-free follow-up.•Infections and adverse events seem to be reduced during drug-free follow-up.•Extended interval dosing may be possible that maintains efficacy and allows for more successful vaccination to new infections.•Extended interval dosing may afford a drug-free pregnancy. Ocrelizumab inhibits relapsing multiple sclerosis when administered every six months. Based on potential similar memory B cell depletion mechanisms with cladribine and alemtuzumab, we hypothesised that CD20-depletion of B cells by ocrelizumab may exhibit a duration of response exceeding the current licenced treatment interval. Internet-located information from regulatory submissions and meeting reports relating to the unpublished open-label, phase II ocrelizumab extension trial (NCT00676715) were reviewed. This followed people (54–55/arm) with MS, who switched from placebo or interferon-beta to ocrelizumab for three 600 mg treatment cycles (week 24, 48, 72) or people treated with ocrelizumab for four 600 mg treatment cycles (week 0–72), followed by an 18 month treatment-free period. CD19+ B cells were rapidly depleted within 2 weeks and slow CD19+ B cell repopulation began about 6 months after the last infusion with median-repletion of over 15 months. The reduced annualized relapse rate during the published efficacy study appeared to be maintained in the extension study and there were no new T1 gadolinium-enhancing or T2 lesions detected in the treatment-free period. Importantly, within these extension cohorts, there appeared to be fewer adverse events and infections events. Ocrelizumab appears to induce durable relapsing disease inhibition, within 3 treatment cycles Therefore, it may be possible to reduce the frequency of dosing to maintain efficacy, whilst limiting infection and other risks associated with continuous immunosuppression and could allow more effective vaccination against new pathogens. Further studies are now clearly required to determine whether this data is robust.